Cytotoxic and apoptosis-inducing activities of the extracts and chemical constituents from the tiger’s milk mushroom, Lignosus rhinocerotis (cooke) ryvarden / Lau Beng Fye - Lau , Beng Fye (2016)
Lignosus rhinocerotis (Cooke) Ryvarden (tiger’s milk mushroom) is regarded as a prized folk medicine by the indigenous communities in Peninsular Malaysia. Scientific validation of the medicinal properties of L. rhinocerotis sclerotium, particularly in treating cancer, is lacking partly due to its rarity. To overcome the problem of supply, artificial cultivation of L. rhinocerotis was attempted. Solid-substrate fermentation on agroresidues yielded the fruiting body and sclerotium while liquid fermentation under shaken and static conditions produced the mycelium and culture broth. Samples of L. rhinocerotis from different developmental stages were also explored as possible sources of cytotoxic compounds. Results from the MTT assay showed that cold aqueous extract of the sclerotium (LRSC-CAE) was active against MCF7 (breast adenocarcinoma) (IC50: 36.7 μg/ml) and HCT 116 (colorectal carcinoma) (IC50: 36.8 μg/ml) whereas for the organic solvent extracts, dichloromethane extract of the pileus (LRCP-DE) was most potent against MCF7 (IC50: 3.8 μg/ml). Both extracts inhibited the growth of MCF7 and HCT 116 cells by inducing G1 cell cycle arrest and apoptotic cell death. Chemical investigations revealed that the cytotoxic activity of LRSC-CAE might be attributed to some heat-labile protein/peptide(s) that could be recovered from the aqueous fraction by ammonium sulfate precipitation. The ethyl acetate and butanol fractions derived from LRSC-CAE contained some low-molecular-weight compounds including palmitic acid (1) and oleamide (2) which demonstrated moderate cytotoxicity. On the other hand, ergosta-4,6,8(14),22-tetraen-3-one (ergone) (3), methyl palmitate (4), methyl linoleate (5), and methyl stearate (6) were identified in LRCP-DE using LC-MS and GC-MS. LRCP-DE was then subjected to bioassay-guided fractionation which lead to the isolation of 9,11-dehydroergosterol peroxide (7) and ergosterol peroxide (8) from L. rhinocerotis for the first time. Steroidal constituents (compounds 3, 7, and 8) inhibited the growth and proliferation of human colorectal cancer cell lines, including HCT 116, HT-29, and DLD-1, but exerted lesser damage on the non-cancerous counterpart, CCD-18Co. In addition, treatment with ergosterol peroxide (8) resulted in cell cycle arrest at G1 phase and apoptotic cell death in both HCT 116 and HT-29 cells that was associated with the collapse of mitochondria membrane potential, externalization of phosphatidylserine, activation of caspases, and DNA fragmentation in a time-dependent manner. Taken together, the nature of cytotoxic components from different developmental stages of L. rhinocerotis, including protein/peptide(s) from the sclerotium and lipophilic constituents, mainly steroids, from the pileus, was clarified. Findings revealed that the cytotoxicity of selected extracts and chemical constituents of L. rhinocerotis were attributed to their ability to induce cell cycle arrest and apoptosis.